Factors associated with blood product requirements during the transoperative period in pediatric patients - Esthela L. Viazcán-Sánchez; Aurora Gómez-Galván; Diana Moyao-García; Jessie N. Zurita-Cruz (Permanyer, 2023)
Background: The efficiency of blood products (BP) requisition in elective non-cardiac surgeries is inherently complex. Moreover, it is aggravated in the pediatric population. This study aimed to identify the factors associated with using less than the requested BP during the transoperative period in pediatric patients undergoing elective non-cardiac surgery. Methods: We conducted a cross-sectional comparative study including 320 patients undergoing elective non-cardiac surgery for whom BPs were requested. Low requirements were considered when less than 50% of the requested amount or no BPs were used, and high requirements when more than the requested amount was used. The Mann-Whitney's U test was applied for comparative analysis, and multiple logistic regression was used to adjust for factors associated with lower requirements. Results: The median age of the patients was 3 years. From 320 patients, 68.1% (n = 218) received less than the requested amount of BP, while only 1.25% (n = 4) received more than the requested amount of BP. Factors associated with transfusion of less than the requested BPs were prolonged clotting time (odds ratio (OR) = 2.66) and anemia (OR = 0.43). Conclusions: Factors associated with lower than requested BP transfusion were prolonged clotting time and anemia.